Tracing Lisbon Metropolitan Area’s Foodscape: Insights from local initiatives and possibilities for future planning policies - Henriques, C. (2022)
In recent years, Lisbon Metropolitan Area (LMA) witnessed the occurrence of various initiatives, highlighting an increasing interest and entrepreneurship in transforming the food system, at both municipal and civil society levels. As sustainability demands become increasingly global, it becomes pivotal for planning policy to understand the mechanisms through which urban actors are pioneering these new ambitions. This paper describes how global goals are being materialized by local actors and practices, insofar as their scope aims to transform this region's food system. Our work is based on a three-fold objective: To characterize such initiatives; study how they're suggesting new food planning agendas in the LMA; and systematize what possible future planning policy can learn from such insights. After an introduction to the territory's planning context and research rationale, a methodological account is provided before completing with a comparing scenario, taken from a 2014 questionnaire among planning officials, with the discourses of 80 initiatives of the public and civil society sectors enquired in 2019. Finally, while using an analytical framework grounded on the recommendations of the Food and Agriculture Organization (FAO) and the Resources Centres on Urban Agriculture and Food Security (RUAF), we flesh out some lessons for future planning policy aiming for long-term sustainability grounded on inter-municipal cooperation and mutual, continuous learning.